Neural control of cardiovascular function in black adults: implications for racial differences in autonomic regulation - Drew, Rachel C. (Am J Physiol Regul Integr Comp Physiol, 2020)
Black adults are at increased risk for developing hypertension and cardiovascular and chronic kidney disease and have greater associated morbidity/mortality than white adults who are otherwise demographically similar. Despite the key role of the autonomic nervous system in the regulation of cardiovascular function, the mechanistic contributions of sympathetic nerves to racial differences in cardiovascular dysfunction and disease remain poorly understood. In this review, we present an update and synthesis of current understanding regarding the roles of autonomic neural mechanisms in normal and pathophysiological cardiovascular control in black and white adults. At rest, many hemodynamic and autonomic variables, including blood pressure, cardiac output, and sympathetic nerve activity, are similar in healthy black and white adults. However, resting sympathetic vascular transduction and carotid baroreflex responses are altered in ways that tend to promote increased vasoconstriction and higher blood pressure, even in healthy, normotensive black adults. Acute sympathoexcitatory maneuvers, including exercise and cold pressor test, often result in augmented sympathetic and hemodynamic responses in healthy black adults. Clinically, although mechanistic evidence is scarce in this area, existing data support the idea that excessive sympathetic activation and/or transduction into peripheral vasoconstriction contribute importantly to the pathophysiology of hypertension and chronic kidney disease in black compared with white adults. Important areas for future work include more detailed study of sympathetic and hemodynamic reactivity to exercise and other stressors in male and female black adults and, particularly, sympathetic control of renal function, an important area of clinical concern in black patients.